The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/cdq.12043
|View full text |Cite
|
Sign up to set email alerts
|

The Life‐Design Group: A Case Study Assessment

Abstract: The life‐design group (LDG) comprises an intervention designed to aid career specialists in helping groups of individuals work through career problems, transitions, and traumas. In this article, the authors describe the LDG and present case study results for 3 undergraduate students who were struggling with gaining movement in their career trajectories. Results indicated decreases in career uncertainty and indecision and increases in readiness for making academic major and career decisions. Although the LDG or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 23 publications
3
26
0
1
Order By: Relevance
“…Research on CCC with both individuals and groups has shown a significant increase in vocational certainty (Cardoso et al, , ; Obi, ), career decision‐making self‐efficacy (Cardoso et al, ; Di Fabio & Maree, ), and career adaptability (Barclay & Stoltz, ; Santilli, Nota, & Hartung, ), as well as a decrease in anxiety and feelings of insecurity (Obi, ).…”
Section: Outcome Research On CCCmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on CCC with both individuals and groups has shown a significant increase in vocational certainty (Cardoso et al, , ; Obi, ), career decision‐making self‐efficacy (Cardoso et al, ; Di Fabio & Maree, ), and career adaptability (Barclay & Stoltz, ; Santilli, Nota, & Hartung, ), as well as a decrease in anxiety and feelings of insecurity (Obi, ).…”
Section: Outcome Research On CCCmentioning
confidence: 99%
“…During the intervention, a client and a counselor form a collaborative relationship, and, through a life‐designing dialogue focused on the reconstruction of meanings, the client's problematic vocational experiences are addressed and the counselor assists the client in resolving his or her career concerns. Research has shown the effectiveness of CCC in achieving these goals (Barclay & Stoltz, ; Cardoso, Janeiro, & Duarte, ; Di Fabio & Maree, ; Obi, ; Rehfuss, Del Corso, Glavin, & Wykes, ). In addition, counseling process research on narrative innovation (Cardoso, Gonçalves, Duarte, Silva, & Alves, ; Cardoso, Silva, Gonçalves, & Duarte, , ) has provided some clues to understanding the process of change during CCC.…”
mentioning
confidence: 99%
“…The thememapping process developed and used by Barclay (2017), Barclay and Stoltz (2015, 2016a, 2016b), and Stoltz and Barclay (2015, in press) in their own career counseling work is beneficial to this process and engages students visually in following the CCI process of identifying patterns and themes in the story and constructing the life portrait. Instructors will want to allow plenty of time for questions from students.…”
Section: Written Exercises In Counselingmentioning
confidence: 99%
“…Likewise, Barclay, Stoltz, and Wolff (2011) delivered a framework for using the CCI in a group setting. Later, Barclay and Stoltz (2016a, 2016b, 2016c) refined the framework and produced initial research supporting the use of the CCI in a group setting. A recent study also supported use of the MCS in a group‐based setting with middle school students (Santilli, Nota, & Hartung, 2019).…”
mentioning
confidence: 99%
“…Suzanne Savickas and Tracy Lara () then offer an interview with former National Career Development Association and American Counseling Association president Lee Richmond to demonstrate how biographical life portraiture promotes clients’ self‐reflection to comprehend continuity and coherence in their life‐career stories. Closing the special issue, Susan Barclay and Kevin Stoltz () introduce and examine a life‐design‐based group career counseling approach, drawing support for its use in promoting career decidedness and educational and occupational choice readiness.…”
mentioning
confidence: 99%